Identification of miR-1256 Signature as a Promising Diagnostic Biomarker in FFPE Tissues of Breast Cancer Patients - Abdullah, Snur Rasool; Hazha Jamal Hidayat (Zanco Journal of Pure and Applied Sciences, 2025)
MicroRNAs (miRNAs) have emerged as promising biomarkers in cancer diagnosis and prognosis, including breast cancer (BC). In this study, we examine whether miR-1256 may be regarded as a powerful biomarker for predicting the prognosis of BC. The expression of miR-1256 was detected in 30 formalin-fixed paraffin-embedded (FFPE) tissue pairs of tumoral samples and their non-tumoral tissues using qRT-PCR. The clinicopathological characteristics of patients relative to miR-1256 expression, along with fold change analysis employing the 2-ΔΔCT method, were also investigated. All statistical analyses were conducted using GraphPad Prism and MedCalc. We found that the miR-1256 level in BC FFPE tissues is notably increased with p < 0.006 and a (2.5367)-fold change compared to control tissues. Also, we analyzed the association between the expression level of miR-1256 and the clinicopathological parameters of BC patients. The overexpression of miR-1256 exhibited no significant correlation with age, tumor grade, tumor size, estrogen receptor (ER) status, human epidermal growth factor-2 (Her-2), or tumor, node, metastasis (TNM) status among patients. The progesterone receptor (PR) status suggested a potential trend (P = 0.077), indicating that low miR-1256 expression was more common in PR-positive subjects. Moreover, the p-value, area under the curve (AUC), Std. Error, sensitivity, and specificity are (0.7039, 0.06709, 0.67, and 0.7, respectively), this signifies a moderate capacity of the test to differentiate between tumors with controls. The results of fold change analysis employing the 2-ΔΔCT method indicated a (2.5367)-fold elevation in miR-1256 expression in tumors relative to controls. This suggests that miR-1256 may have an oncogenic role in carcinogenesis, potentially promoting BC development. As a result, we demonstrated that elevated miR-1256 expression correlates with the progression of BC, indicating that miR-1256 may be associated with oncogenic processes in BC tumorigenesis and progression.